Carbon dots based immunosorbent assay for the determination of GFAP in human serum. (15th February 2018) - Ma, Yunsu; Xu, Guanhong; Wei, Fangdi; Cen, Yao; Song, Yueyue; Ma, Yujie; Xu, Xiaoman; Shi, Menglan; Sohail, Muhammad; Hu, Qin
Abstract: Glial fibrillary acidic protein (GFAP) is expressed in the central nervous system and the level of GFAP normally rises with brain injury and astroglial tumors. So, serum GFAP is used as a marker for diagnosing various types of brain damage and astroglial tumors. In this study, a new sensor based on carbon dots (CDs) linked with antibodies to specifically detect GFAP in human serum was developed. Anti-GFAP (Ab1) linked with protein A/G agarose resin (PA/G) as a capture antibody (PA/G-Ab1) and anti-GFAP (Ab2) labeled with CDs as a detection antibody (CDs-Ab2) were prepared firstly. Then the CD-linked antibody immunosorbent assay (CLAISA) method was constructed based on the sandwich conjunction reaction among PA/G-Ab1, GFAP, and CDs-Ab2. CLAISA, using the fluorescence of PA/G-Ab1-GFAP-Ab2-CDs as the direct signal, enabled the proposed immunosensor to detect GFAP sensitively with a linear range of 0.10–8.00 ng ml −1 and a detection limit of 25 pg ml −1 . This method was applied to the determination of GFAP in human serum by the standard addition method, and the results showed high accuracy and precision. Considering the easy synthetic process and excellent performance of CLAISA, this method has great potential to be used to monitor GFAP in the clinic.